ANALYSIS OF RELATIONSHIP AMONG STAKEHOLDER PRESSURES, ENVIRONMENTAL MANAGEMENT ACCOUNTING USE, STRATEGY, AND INNOVATION: AN EMPIRICAL EVIDENCE FROM INDONESIA - Arum Dwi Jayanti; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
As an increased awareness of a global issue regarding the environmental impact of business activity; this study aims to examine the relationship among stakeholder pressures, environmental management accounting use, strategy, and innovation. This study is performed by conducting the survey to management accountants and environmental managers of companies in Indonesia. The convenience sampling technique was used and resulted in 34% response rate. The hypothesis testing was conducted by using Structural Equation Modeling (SEM) with SmartPLS 2.0 software. The results are: (1) the stakeholder pressures have a positive effect on EMA use, (2) the prospector strategy has no positive effect on EMA use, (3) EMA use has a positive effect on process innovation, but not with product innovation, (4) the prospector strategy has a positive effect on process innovation as well as on product innovation.